THE PERCEPTION OF GRADUATES OF VOCATIONAL EDUCATION ABOUT PHYSICAL EDUCATION (Fiep Bulletin - online, 2010)
In this article we seek to experience the practice of tasks performed by graduates of the Agricultural Technical Course in INDEA - Institute of Agricultural Defense of the State of Mato Grosso, and identify their perception of Physical Education offered in the period of their formation, making their historical correlation about teaching physical education in Brazil, the changes that have occurred, and seeking to improve the current teaching practice of teaching and learning practiced in Vocational Education. This is a qualitative research, where a questionnaire was mixed, interview and follow-up activities, with experts in agriculture, fiscal agents of defense agriculture and forestry, working in the URS / ULE Caceres, working in the border-Brazil Bolivia. Both aged 45 to 50 years, 80% formed the Federal Network. We know a new reality of work that our students may face, providing support that will improve the practice within the school.
Keywords: Agricultural Education; Professional Education; Physical Education; Teaching and learning